Characterization of chitosan from extracted fungal biomass for piezoelectric application - Ahmad, Farah; Mohd Hatta, Maziati Akmal; Amran, Anisah; Hasni, Mohd Haffizi (IOP Publishing Ltd, 2020)
Conventional piezoelectric materials from piezoceramic and polymer are non-renewable and could be toxic in nature, which limit its application in biomedical application. Chitosan, which is a natural polysaccharide, has the potential to be used as piezoelectric biomaterial which may provide the solution for toxicity, non-biodegradability and non-biocompatibility issues of conventional piezoelectric materials. Chitosan may be produced sustainably through extraction from fungal cell walls. This study aims to characterize chitosan extracted from fungi Aspergillus oryzae for piezoelectric application. A. oryzae was cultivated on modified Sabouraud dextrose broth medium. Alkaline treatment was performed on fungal biomass using 1 M NaOH for extraction and deacetylation of chitosan at 100 °C for 1 hour. Fourier transform infrared spectroscopy results showed that the broad absorption band that corresponds to hydrogen bonded O-H stretching vibrations overlapped with N-H stretching band. X-ray diffraction analysis confirmed the semicrystalline nature of the chitosan sample. Piezoelectric properties can be attributed to intrinsic molecular polarization arising from the noncentrosymmetric crystal structure.